Construction of a Microfluidic Platform With Core-Shell CdSSe@ZnS Quantum Dot-Encoded Superparamagnetic Iron Oxide Microspheres for Screening and Locating Matrix Metalloproteinase-2 Inhibitors From Fruits of Rosa roxburghii - Tao, Yi; Pan, Meiling; Zhu, Fei; Liu, Qing; Wang, Ping (Frontiers in Nutrition, 2022)
Microfluidic platform is a versatile tool for screening and locating bioactive molecules from functional foods. Here, a layer-by-layer assembly approach was used to fabricate core-shell CdSSe@ZnS quantum dot encoded superparamagnetic iron oxide microspheres, which served as a carrier for matrix metalloproteinase-2. The matrix metalloproteinase-2 camouflaged magnetic microspheres were further incorporated into a homemade microfluidic platform and incubated with extracts of fruits of Rosa roxburghii. Flow rate of the microfluidic platform was tuned. The major influencing parameters on ligand binding, such as dissociate solvents, incubation pH, ion strength, temperature, and incubation time were also optimized by using ellagic acid as a model compound. The specific binding ligands were sent for structure elucidation by mass spectrometry. The absolute recovery of ellagic acid ranged from 101.14%–102.40% in extract of Rosa roxburghii under the optimal extraction conditions. The linearity was pretty well in the range of 0.009 mg·mL-1–1.00 mg·mL-1(R2=0.9995). The limit of detection was 0.003 mg·mL-1. The RSDs of within-day and between-day precision were less than 1.91%. Thirteen ligands were screened out from fruits of Rosa roxburghii, which were validated for their inhibitory effect by enzyme assay. Of note, eleven new matrix metalloproteinase-2 inhibitors were identified, which may account for the anti-tumor effect of fruits of Rosa roxburghii.